2021
DOI: 10.1016/j.ssmph.2021.100833
|View full text |Cite
|
Sign up to set email alerts
|

Has the relationship between wealth and HIV risk in Sub-Saharan Africa changed over time? A temporal, gendered and hierarchical analysis

Abstract: This study examines the relationship between wealth and HIV infection in Sub-Saharan Africa to determine whether and how this relationship has varied over time, within and across countries, by gender, and urban environment. The analysis draws on DHS and AIS data from 27 Sub-Saharan African countries, which spanned the 14 years between 2003 and 2016. We first use logistic regression analyses to assess the relationship between individual wealth, HIV infection and gender by country and year stratified on urban en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Until recently, multiple studies had found a positive association between wealth level and HIV status. Our results support the recent Andrus study findings that the positive association between HIV and wealth has weakened over time [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Until recently, multiple studies had found a positive association between wealth level and HIV status. Our results support the recent Andrus study findings that the positive association between HIV and wealth has weakened over time [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, men in relatively poorer households may have little to no spare time for HIV testing uptake with a daily round-the-clock focus on making ends meet [ 49 , 57 59 ]. Additionally, Sub-Saharan Africa has been noted to have higher HIV infection rates among wealthier individuals compared to poorer individuals, unlike the global norm, which may also explain the increased likelihood of testing [ 61 ]. Similarly, possession of health insurance addresses financial barriers to accessing care.…”
Section: Discussionmentioning
confidence: 99%
“…The high HIV prevalence in our cohort might reflect HIV infection in the general population. In 2020, Namibia was ranked as the 6th highest rate of HIV in the world [ 49 ] and 5th in the SSA between 2003 and 2016 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%